(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
The present study aimed to analyze and compare the morphometric and meristic characteristics of Botia dario and Botia lohachata through a systematic approach involving morphometric measurements, meristic counts, and external morphological observations. A total of twenty-two morphometric parameters and five meristic characters were measured and statistically analyzed. The results revealed significant differences between the two species across several measured traits. These findings contribute to accurate species identification and provide clear diagnostic features for distinguishing B. dario from B. lohachata. Consequently, this study offers valuable insights for systematic classification and supports effective stock conservation and management strategies for these economically and ecologically important fish species in Bangladesh. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 567-573